Situasi Dedaktis Pembelajaran Pada Materi Kesamaan Dua Matriks SMA - Nurgita, Eprilia; Kesumawati, Nila; Fuadiah, Nyiayu Fahriza (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to identify the didactic situation of learning obstacles faced by grade XI students at SMA Negeri 1 Gelumbang in learning the material of the similarity of two matrices. The research method used is qualitative, with data collection through observation, interviews, documentation, and written tests. The data analysis process includes data reduction, data presentation, and drawing conclusions based on valid evidence. The results of the study indicate that students are less active in learning when researchers apply the Learning Obstacle situation design that occurs in the material of the similarity of two matrices, namely; 1) difficulty in understanding the concept of the similarity of two matrices, 2) difficulty in completing the operation of the similarity of two matrices, 3) difficulty in completing the operation of addition and subtraction of matrices. This study is expected to provide recommendations for improving teaching for students, teachers, and schools in order to improve the quality of mathematics learning and encourage students’ interest and motivation in learning.